Revisiting an ancient treatment for transphincteric fistula-in-ano 'There is nothing new under the sun' Ecclesiastes 1v9. (December 2015) - Soliman, F; Sturgeon, G; Hargest, R
Objective: The history of treatments for fistula-in-ano can be traced back to ancient times. Current treatment of transphincteric fistulae is controversial, with many options available. We reviewed the history of treatment using cutting setons and present our series of transphincteric fistulae in the light of the series in the literature. Design: Literature review and case series. Setting: Hospital based coloproctology service Participants: 140 consecutive patients presenting with fistula-in-ano were included. Main Outcome Measures: The literature pertaining to treatment of transphincteric fistula was reviewed, along with the outcome of various treatment methods for this condition. Data were collected for 140 consecutive patients presenting with fistula- in-ano were assessed for fistula healing, recurrence and complications. Results: A total of 140 consecutive patients with fistula-in-ano were identified, of which 111 were cryptoglandular (79.3%). Eighty-one of these 111 were transphincteric (73.0%). At a median follow-up of 35 months (range, 2–83 months), 70 transphincteric fistulae had healed (86.4%), 10 were still undergoing treatment (12.3%) and one patient was lost to follow-up prior to treatment (1.2%). Two patients in this group required a stoma (2.5%), six patients developed recurrence (7.4%); three 'true' recurrences (3.7%). One (1.2%) developed a chronic fissure. There were no reported cases of incontinence. Conclusions: The management of transphincteric fistula-in-ano is complex and controversial, for which no clear surgical procedure has gained acceptance as the gold standard. This study demonstrates that transphincteric fistulae can be successfully treated using cutting setons. A high healing rate (86.4%), low recurrence rate (7.4%) and a low complication rate (3.7%) are shown, which compares favourably with published rates over a long follow-up.